Zooplankton Community Composition in Floodplain Lakes of Caura River, Venezuela - Reverol, Yinett; Delgado, José; López, Carlos; Sánchez, Luzmila (Boletín del Centro de Investigaciones Biológicas, 1970)
Four floodplain lakes (Chuapo, Naparaico, Brava and Aricagua) on the lower basin of the Caura River, Venezuela were analyzed regarding composition of the zooplankton. Samples were collected monthly from March 1998 to February 2000. At each site, composite water samples were filtered through a 60-Î¼m mesh plankton net, fixed in 10% formalin solution and preserved in 70% ethanol. Copepods were separated into adults and nauplii. A total of 101 species (68 rotifers and 33 cladocerans) were identified. The most abundant rotifer species were Brachionus zanhiseri var. gessneri, B. zanhiseri f. reductus and Keratella americana. Bosminopsis deitersi was the most dominant species among cladocerans. Nauplii and calanoids were the most abundant copepods. Mean abundance per lake was: Aricagua (390,18 org/L), Brava (261,03 org/L), Naparaico (193,21 org/L) and Chuapo (170,00 org/L). Total zooplankton abundance showed a strong seasonal trend in the floodplain lakes, increasing during low waters (dry season) and declining in rising waters (rainy season). We observed a succession of frequent dominant species, instead of one dominant species.